Pengaruh Asap Cair Berbahan Baku Pelepah Kelapa Sawit Sebagai Koagulan pada Kualitas Karet Krep - Saputra Saputra; Ersan Ersan; Muhammad Rofiq (Jurnal Agro Industri Perkebunan, 2016)
Public rubber platation Indonesia reached 80% from the vast number of rubber Indonesia. But people rubber low quality, because the use of coagulant is not advice. The researc aims to use liquid smoke from midrib plam oil as an alternative coagulants formic acid to maintain the quality of crepe rubber. Dose of liquid smoke from midrib plam oil 4, 6, 8, 10, 12, and 14% given in each treatment 250 ml latex and will be tested pH, long clotting time, dry rubber content, plasticity retention index (PRI), leves of substance evaporates, until ash, and levels of dirt in acordance with the SNI 1903 : 2000. Tests conducted in te laboratory PTPN VII business Wwy Unit Berulu, Pesawara, Lampung. The results showed a dose of liquid smoke 4 â€“ 12% crepe rubber produce with quality SIR 10, long clottng time dose treadment liquid smoke 14% but quality is only reached SIR 20 and dose treadment liquid smoke from midrib plam oil is best dosage 8% v/v.Keywords: crepe rubber, latex coagulant, liquid smoke, oil palm frondPermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/35